A COMPARATIVE STUDY OF DENTAL TERMINOLOGY IN UZBEK AND ENGLISH LANGUAGES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article explores the linguistic structures and terminological systems associated with dental terminology in both Uzbek and English. Through comparative analysis, the research highlights differences and similarities in the cultural and scientific development of dental language, including etymology, morphology, and semantic fields. The findings may contribute to better understanding and more effective translation in medical and academic contexts.